2018
DOI: 10.2337/db18-399-p
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hypoglycemia Rates Are Highest among those with Suboptimal Reporting Behaviour—Results from the InHypo-DM Study

Abstract: Many patients fail to report severe hypoglycemia (SH) events to their healthcare provider (HCP). This limits the ability of HCPs to adjust treatment regimens and optimize glycemia. This study aimed to explore the independent association between patients’ disclosure of SH events to their HCP and self-reported rates of SH. Data were obtained from the InHypo-DM population-based study, Canada’s largest hypoglycemia-specific survey. To indicate SH disclosure, patients at risk for hypoglycemia rated how often they r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…55,56 Onymous versus anonymous self-report has been shown to underestimate SH frequency by 50-65%. 11,28 We further applied multiple backstops to attenuate information bias. Namely, we standardized questionnaires; incorporated validated measures; gathered comprehensive information to jog episodic recall; and gave participants up to 7 days to review and reflect on items before responding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…55,56 Onymous versus anonymous self-report has been shown to underestimate SH frequency by 50-65%. 11,28 We further applied multiple backstops to attenuate information bias. Namely, we standardized questionnaires; incorporated validated measures; gathered comprehensive information to jog episodic recall; and gave participants up to 7 days to review and reflect on items before responding.…”
Section: Discussionmentioning
confidence: 99%
“…Web‐based, compared to postal‐ or telephone‐based, survey modes are generally more effective at eliciting accurate and honest reporting, 54 primarily because they demand little personally identifiable data 55,56 . Onymous versus anonymous self‐report has been shown to underestimate SH frequency by 50‐65% 11,28 . We further applied multiple backstops to attenuate information bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, PWD under-reporting of hypoglycemia (e.g. due to perceived consequences on the PWDs’ careers or driver’s licenses) has been identified as a major problem in clinical care [11, 12]. This is further demonstrated by higher observed rates of hypoglycemia in studies that utilize self-reported data as opposed to sourcing data from clinical trial settings [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaires are a preferred method for ascertaining level 3 hypoglycaemia epidemiology: (a) most events are not clinically documented; (b) the lack of a standard BG threshold for SH diminishes the relevance of glucometer data; and (c) deliberate patient non‐disclosure 14,15 and provider under‐recognition 16,17 occlude accurate event assessment at point‐of‐care. Research shows that online questionnaires, which demand little personally identifiable data, are more effective than postal or telephone modes at motivating participation and honest reporting 18,19 .…”
Section: Methodsmentioning
confidence: 99%